Symptomatic Hyponatremia after Bowel Preparation: Report of Two Cases and Literature Review - Costa, Juliana Moura (2017)
Introduction: Bowel preparation for colonoscopy and/or colorectal surgery can cause electrolyte imbalances. The risk of electrolyte imbalances seems to be related to the type of bowel cleansing solution, age of patients and comorbidities.Case Report: We report two cases of symptomatic hyponatremia (focal neurological signs and coma) after bowel preparation with sodium picosulfate/magnesium citrate for colonoscopy. In both cases, symptoms related to hyponatremia rapidly disappeared after sodium level correction with intravenous administration of hypertonic saline (3% NaCl).Discussion: Electrolyte imbalances are more common with sodium phosphate-based solutions (NaP) and sodium picosulfate/magnesium citrate, in patients older than 65, in patients treated with thiazide diuretics, angiotensin-converting-enzyme inhibitor, betablockers or antidepressants and in gastrectomized patients. These patients should use macrogol-based solutions (polyethylene glycol).Conclusion: In patients at risk (patient > 65 years old, patients taking thiazide diuretics, angiotensin-converting-enzyme inhibitors, beta-blockers and antidepressants and with previous gastrectomy) we recommend macrogol-based solutions.